Effect of Implant Number, Distribution with Different Attachments on the Retention and Stability of Implant Supported Overdenture - Abdulamajeed, Areej Mufeed; Hasan, Radhwan H. (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2017)
It was stated that the “PREVENTION IS BETTER THAN CURE” Today, with the more attention on preventive measures in prosthodontics, the use of implant supported overdenture has increased to the point where it is now a feasible alternative to most treatment plan outlines in the construction of prosthesis for patients (Sheldon Winkler, 2009). Evaluate the effect of number and distribution of an implant upon in vitro retention and stability of a simulated implant-supported overdenture. In this in-vitro experimental study a model simulating a mandibular edentulous ridge with 7 dental implants analogs inserted in the model approximating the tooth position in the natural dentition was constructed. A two overdenture housing for each type of attachment made of acrylic resin with three hooks attach to occlusal surface of it which connected to three chains attached to a force gauge testing machine was used to measure peak load (N) required to disconnect (dislodge) an attachment in three directions vertical, rotational and oblique. Two different type of attachments have been studied (Ball, Locator). This study was aimed to evaluate retention and stability of implant-retained overdentures based upon implant number and distribution. One way ANOVA analysis of variance test indicated that there were significant differences at P<0.05, using Duncan`s Multiple Range Test for comparison among the groups of Ball and Locator attachment indicated that groups of multi implants recorded the significantly higher measured peak load (N) in the three directions of dislodgement variation in implant`s number and distribution affect the retention and stability of implant supported overdenture according to type of attachment utilized.